Cash transfers and poverty reduction in South Africa: a case study of old age pensions - Kasere, Gayle Farai (Rhodes University, Faculty of Humanities, Department of Sociology, 2012)
Social assistance in the form of cash grants is a large and fiscally costly component of anti-poverty policy in South Africa. A critical question arises: Are the grants effective tools for reducing poverty in South Africa and, moreover, how significant is their impact on poverty? As a measure of reducing poverty, the government has expanded the social grants system since the advent of the new democracy in 1994. The country's social grant system is quite comprehensive and it is intended to cover vulnerable individuals over their life course from childhood to adulthood and into old age. Policy discourse surrounding the grants centres on the sustainability of the system and its implications for socio-economic development and poverty alleviation. It is therefore important that the significance of grants is identified and assessed particularly in relation to very poor households. This dissertation focuses specifically on one particular grant, namely, the old age pension. It does so in the context of the sustainable livelihoods conceptual framework and the history of the social grant system in South Africa. Statistical data collected by the South African government as well as more localised evidence gathered in the Eastern Cape town of Grahamstown is used to ascertain the significance of old age pensions for poverty reduction. While there is some evidence to suggest that pensions contribute to poverty reduction, this does not translate into poverty alleviation. In fact, there is some unevenness in the impact of pensions on poverty. In this regard, the decision-making structures in poor households regularly influence the way pension money is allocated and used within households. Grant money is normally shared in extended households, such that the pension does not simply benefit the recipient but the recipient's household as a whole. Although there is cause for concern regarding the propensity of social grants to affect people's behaviour negatively, there is a case to be made for retaining grants as an important, though not the only, form of anti-poverty strategy. This highlights the need for continued research on the social grant system and pensions more specifically.
Keywords: Poverty -- Economic aspects -- South Africa -- Eastern Cape; Poverty -- Grahamstown -- Eastern Cape; Social security -- South Africa; Pensions -- South Africa